The Role Of Digital Technologies In Economic Development: Foreign Experience - Odiljonovna, Turaeva Nafisa (Journal of Higher Education and Academic Advancement, 2024)
This article reflects on the foreign experience of using digital economy technologies in our country and provides an analysis of the use of digital economy. In addition, the work carried out on the application of the digital economy in Uzbekistan and the reforms carried out by the government, the possibilities of the digital economy, the features of cost reduction and the opinions on the use of information and communication technologies that contribute to its development are described.